Theology in the context of world Christianity : how the global church is influencing the way we think about and discuss theology - Tennent, Timothy C. (Grand Rapids, MI, Zondrvan, 2007)
It is no secret that the center of Christianity has shifted from the West to the global South and East. As the gospel penetrates new cultures and new situations, it must answer new questions and be restated in new ways. While the truths of the Christian faith are timeless and universal, new contexts bring new understandings. What does all this mean for the discipline of theology? The underlying assumption of many is the normativity of Western theological formulation. Is this still a valid premise? Or is the Christian faith not only culturally translatable, but also theologically translatable? Timothy Tennent answers this question with a resounding yes. Theological reflection is alive and well in the Majority World church and needs to be heard, considered, and brought into conversation with Western theologians -- and not just among missionaries and missiologists. Tennent examines traditional theological categories in conversation with theologians from across the globe, making this volume valuable for students, pastors, missionaries, and theologians. - Back cover.
As Christianity advances in the South and East, its universal truths face new questions and are expressed in new ways. Majority world theological reflection needs to be brought into conversation with Western theology. Doing so will uncover blind spots and biases and will bring a potentially revitalizing agent into the Western church.
The emergence of a global theological discourse -- Theology : is the Father of Jesus the God of Muhammad? -- Bibliology : Hindu sacred texts in pre-Christian past -- Anthropology : human identity in shame-based cultures of the Far East -- Christology : Christ as healer and ancestor in Africa -- Soteriology : is "salvation by grace through faith" unique to Christianity? -- Pneumatology : the Holy Spirit in Latin American Pentecostalism -- Ecclesiology : followers of Jesus in Islamic mosques -- Eschatology : Jonathan Edwards and the Chinese Back to Jerusalem movement -- The emerging contours of global theology.
Includes bibliographical references and index.
Keywords: Theology -- Methodology; Globalization -- Religious aspects -- Christianity